Efficacy and Safety of Dipeptidyl Peptidase-4 Inhibitor Compared to Sulphonylurea in Type II Diabetes Patients Inadequately Controlled with Metformin Alone - Palikhey, Anjan; Karki , Manoj; Shrestha, Jharana; Shrestha, Laxmi; Shrivastava, Amit Kumar; Yadav, Chandrajeet Kumar; Rayamajhi, Bidhata (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Diabetes is a metabolic disorder marked by high blood glucose levels, and treatment often requires multiple drugs to achieve adequate glycemic control. In individuals with type 2 diabetes mellitus who do not respond to Metformin, doctors may prescribe a Dipeptidyl Peptidase-4 inhibitor or a Sulphonylurea as potential add-on therapy. The study was conducted to compare the efficacy and safety of the Dipeptidyl Peptidase-4 inhibitor with Sulphonylurea. MATERIAL AND METHODS This was an interventional, comparative study involving 100 type 2 diabetic patients who visited the Medicine department at Universal college of Medical Sciences. All the eligible patients were randomly divided into two treatment groups (50 each): Group A (Sulphonylurea + Metformin) and Group B (Dipeptidyl Peptidase-4 inhibitor + Metformin). Treatment was provided for 18 weeks, and patients were investigated for blood glucose parameters like glycosylated hemoglobin, fasting blood glucose, postprandial glucose at baseline and after 18 weeks of follow-up, and questions regarding adverse reactions. The efficacy of the drugs between the two treatment groups was compared using an independent t-test. RESULTS Dipeptidyl Peptidase-4 inhibitor plus Metformin was found to be superior to Sulphonylurea plus Metformin in terms of HbA1c-lowering efficacy (p=0.030). A total of 26% of patients in the Sulphonylurea group reported unpleasant hypoglycemic events, compared to 6% in the Dipeptidyl Peptidase-4 inhibitor group (p=0.006). Patients treated with Sulphonylurea gained weight over 18 weeks, but those on Dipeptidyl Peptidase-4 inhibitor lost weight (p=0.043). CONCLUSION Compared to Sulphonylurea, adding a Dipeptidyl Peptidase-4 inhibitor to a Metformin therapy significantly improves glycaemic control in type 2 diabetic patients who are not well controlled with Metformin monotherapy, without producing hypoglycemia or weight gain.